Keabsahan Hukum Kebijakan Transfer Kuota Domestic Market Obligation (DMO) Batu Bara - Alkanu, David Pandu; Negara, Tunggul Anshari Setia; Istislam, Istislam (Universitas Negeri Malang, 2020)
This study aimed to analyze the legal validity of the DMO policy which was based on the Minister of Energy and Mineral Resources Letter 2783/32/MEM.B/2018 dated April 19, 2018, and the legal implications of the DMO quota transfer policy on mining companies. This research was a normative study using a statute approach. The results showed the coal DMO quota transfer policy was a policy that recognized its existence and had binding legal force. The DMO quota transfer policy had implications for fulfilling quotas for mining companies that contract with State Electricity Enterprise and mining companies that did not contract with State Electricity Enterprise. Mining companies that contract with State Electricity Enterprise could buy and sell coal which was more than the 25% coal DMO obligation with State Electricity Enterprise. Quota transfers made by mining companies that did not contract with State Electricity Enterprise had an uncertain price.